HERMES (Hermeneutic Resonance of Muslim Family Ethics and Syariah) Model Penafsiran Hadis Berbasis Hikmah Bukan Alat Legitimasi Otoritatif - Liddinillah, Muhammad Yakhsyallah; Sar'an, Mohamad (Interdisciplinary Explorations in Research Journal, 2025)
Studies of ḥadīth on family law in contemporary Islamic discourse frequently become trapped in ahistorical and literalistic approaches. This tendency can be seen in the reading of ḥadīths related to polygamy, divorce, child marriage, and wifely obedience, which are often reduced to mere normative legitimization without considering historical context, maqāṣid al-sharīʿah, and the challenges of modern families. This article proposes a new framework called HERMES (Hermeneutic Resonance of Muslim Family Ethics and Sharīʿah) as an alternative paradigm. HERMES emphasizes that ḥadīth is not merely a static text, but a living resonance of prophetic values that interacts across time. This study employs a qualitative approach using library research and critical-hermeneutic analysis. The data are drawn from primary sources in the form of classical ḥadīth collections and their commentaries, as well as secondary sources consisting of contemporary studies on family law, maqāṣid al-sharīʿah, and modern hermeneutical theories. The analysis combines an ahistorical critique of literalistic interpretations with a transdisciplinary construction involving sociology, psychology, and the philosophy of law. HERMES is structured around four dimensions: (1) hermeneutic resonance, namely historical–contextual reading; (2) ethical resonance, which involves extracting the values of justice, compassion, and public benefit (maṣlaḥah); (3) social resonance, which connects ḥadīth with contemporary issues such as digital divorce, child marriage, and domestic violence; and (4) sharīʿah resonance, which reaffirms maqāṣid as the primary objective of family law. Through this approach, the article demonstrates that HERMES can serve as an epistemological foundation for reformulating Islamic family law to be more adaptive, just, and relevant.